Femicide. From feminist theory to peruvian criminal law - Rodríguez Vásquez, Julio Alberto (2023)
This article addresses the evolution of the category of femicide. It studies its birth in feminist theory, its translation and development in Latin American academia, its use in international law and its transformation into a crime. The analysis of the evolution of this concept allows highlighting its singular and autonomous character. Thus, the study of this category helps to strengthen the doctrine that defines femicide as the killing of a woman for gender reasons, that is, the killing of a woman in a context in which the victim failed to comply with gender stereotypes.